North American public opinion on health and smoking - Duch, R; Tedin, K; Williams, L (Oxford University Press, 2018)
Public opinion regarding smoking and health has been of interest to polling companies since the 1940s. This article documents the rate of change in the public’s awareness and beliefs about smoking and health in North America (the United States and Canada). It reports on four broad categories of opinions: public awareness of reports that smoking has been linked to lung cancer; beliefs that smoking is harmful to health and a cause of lung cancer; beliefs that smoking is a cause of diseases other than lung cancer; and beliefs about the health hazards of secondhand smoke.